Effects of iodized salt on the physico-chemical parameters and the sensoryproperties of dry-cured pork loin - Lušnic Polak, Mateja (Array, 2018)
In the meat industry sea salt is usually used for dry-cured meats, for few products iodized salt (or table salt), and for most pasteurized and sterilized meat products nitrite salt is used. The main ingredient of nitrite salt is non-iodized (evaporated) salt. The aim of present study was to examine if the use of sea salt or iodized sea salt instead of non-iodized (evaporated) salt affects the physico-chemical parameters and sensory characteristics of dry-cured meat. For this purpose, three experimental groups of dry-cured pork loins were prepared: group produced from fresh loins with not-iodized sea salt, group produced with iodized sea salt, and group produced with evaporated non-iodized salt, as control. Analyses of dry-cured pork loins included physicochemical analysis of basic composition, measuring lipid oxidation product (the thiobarbituric acid reactive substances and peroxide number), thermodynamic water activity, instrumental analysis of colour with chromometer Minolta CR-200b, as well as sensory analysis using the method of quantitative descriptive analysis. Introducing iodized sea salt (with declared 26 to 39 mg potassium iodide/kg and determined 15 mg of I/kg) showed that iodine cannot accelerate lipid and colour oxidation, but evaluation of sensory attributes indicated perceived rancid odour and flavour compared to control group (evaporated non-iodized salt) of dry-cured pork loins.